Clinical differentiation of cutaneous and subcutaneous mast cell tumors in dogs: A pilot study - Teruo Itoh; Atsuko Kojimoto; James Chambers; Kazuyuki Uchida; Hiroki Shii (Open Veterinary Journal)
Background: Canine mast cell tumors (MCT) in the skin are classified into cutaneous (cMCT) and subcutaneous (scMCT) types, which exhibit different clinical behaviors. Although these types have been classified only by histology, preoperative differentiation is important for proper surgical planning.